Factors contributing to the success of accounting simulation game / Ju Anizai Zaini - Zaini, Ju Anizai (2014)
Nowadays, teaching pedagogy is varied in the globalized world such as simulation games. It is very important to choose an interesting pedagogy of teaching and learning to encourage students with basic accounting background. Lecturers must guide them to face their inability to understand accounting problems. This is so that the students will be more focussed and abled to perform better. The purpose of this study is to examine the relationship among three independent variables which are accounting simulation game-syllabus fit, perceived usefulness of the computerized accounting system and computer self-efficacy, with a dependent variable which is the effectiveness of accounting simulation game. The contribution of this study is to enrich the ideas of teaching and learning pedagogy and to introduce a new method of teaching and learning called as the accounting simulation game. The sample of this study are non-accounting students from UiTM Terengganu. The students need to take this basic financial accounting course in order to fulfil the requirements for their graduation. A set of self-administered questionnaire was distributed to the participants at the end of the session of the games. The results disclosed that there is a significant moderate positive relationship between the independent variables and the dependent variable. Besides that, the descriptive analysis also explained the demographic data and the extent of indulgence created from the game towards the basic financial accounting knowledge. As a conclusion, the independent variables were the factors contributing to the success of an accounting simulation game. Therefore, all the hypotheses were accepted.